Energy-gaining Principle of Driving Circuit in High Voltage Var Compensation Device - 杨磊; 张正宏; 徐振 (Kongzhi Yu Xinxi Jishu)
Associating with the working characteristics of TCR, TSC and SVG, it introduced the energy-gaining methods and principles of their driving circuits or trigger circuits . Meanwhile, a general low-voltage energy-gaining method was proposed, and the advantages and disadvantages of various energy-gaining methods were compared.